2022
DOI: 10.1021/acs.jpcb.2c07647
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence of Bimolecular Guanine Quadruplexes: From Femtoseconds to Nanoseconds

Abstract: The paper deals with the fluorescence of guanine quadruplexes (G4) formed by association of two DNA strands d(GGGGTTTTGGGG) in the presence of K + cations, noted as OXY/K + in reference to the protozoon Oxytricha nova, whose telomere contains TTTTGGGG repeats. They were studied by steady-state and timeresolved techniques, time-correlated single photon counting, and fluorescence upconversion. The maximum of the OXY/K + fluorescence spectrum is located at 334 nm, and the quantum yield is 5.8 × 10 −4 . About 75% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…This means that a helical geometry alone is not sufficient to give rise to HENE. In contrast, it was detected for a four-stranded structure (G-Quadruplex) formed by association of two identical DNA strands d­(G 4 T 4 G 4 ) in the presence of K + cations . For this system, a long-lived fluorescence with a lifetime of 2.1 ns was observed at 315 nm, representing 10.8% of the photons emitted at this wavelength.…”
Section: The Show Case: (Dgc) N ·(Dgc) Nmentioning
confidence: 86%
See 2 more Smart Citations
“…This means that a helical geometry alone is not sufficient to give rise to HENE. In contrast, it was detected for a four-stranded structure (G-Quadruplex) formed by association of two identical DNA strands d­(G 4 T 4 G 4 ) in the presence of K + cations . For this system, a long-lived fluorescence with a lifetime of 2.1 ns was observed at 315 nm, representing 10.8% of the photons emitted at this wavelength.…”
Section: The Show Case: (Dgc) N ·(Dgc) Nmentioning
confidence: 86%
“…A short description of HENE was reported recently in our account of intrinsic DNA fluorescence . In the meantime, new studies ,, rendered the assessment of the excited states responsible for this intriguing emission much more complex than that proposed by the first computational approaches. , Therefore, we have decided to revisit the current state of knowledge of this poorly understood, yet ubiquitous, fluorescence emission in the present Perspective. After presenting an overview of the most striking results, we highlight the importance of HENE relative to LENE in the steady-state fluorescence spectra of duplexes, discuss potential connections with structural and electronic issues, stress the need for further computational studies, and provide experimental tips that are crucial for more refined studies.…”
Section: The Show Case: (Dgc) N ·(Dgc) Nmentioning
confidence: 95%
See 1 more Smart Citation
“…Note that previous research, based mainly on the steady-state measurements, has observed substantial influences of the loop and/or dangling bases on the yield and maximum intensity wavelength of GQ fluorescence. ,, Recent studies on BGQ/Na + reported a strong CT state between a thymine in a loop and a guanine in the outer tetrad; , whether this state may contribute to the fluorescence of BGQ/Na + has however remained unresolved. On the other hand, it was observed in a very recent time-resolved study that thymines in loops are responsible for a weak low-energy excimer emission (at ∼445 nm) derived from comparison of steady-state fluorescence for a bimolecular DNA GQ formed by dG 4 T 4 G 4 . In light of this, the capture and identification of the ∼475 nm transient fluorescence provide the first time-resolved evidence for participation of loop nucleotides through CT in the deactivation and intrinsic fluorescence of GQ.…”
mentioning
confidence: 84%
“…On the other hand, it was observed in a very recent time-resolved study that thymines in loops are responsible for a weak low-energy excimer emission (at ∼445 nm) derived from comparison of steady-state fluorescence for a bimolecular DNA GQ formed by dG 4 T 4 G 4 . 53 In light of this, the capture and identification of the ∼475 nm transient fluorescence provide the first time-resolved evidence for participation of loop nucleotides through CT in the deactivation and intrinsic fluorescence of GQ. The result therefore improves understanding of the origin of the complex fluorescence from GQs.…”
mentioning
confidence: 93%